1996
DOI: 10.1007/bf01567962
|View full text |Cite
|
Sign up to set email alerts
|

Light and scan electron microscopic analysis of cyclops syndrome: etiopathogenic hypothesis and technical solutions

Abstract: The loss of range of motion after anterior cruciate ligament (ACL) reconstruction is one of the most common and most challenging complications of this kind of surgery. Recently, an intercondylar notch fibrous proliferation, called cyclops syndrome because of its arthroscopic appearance, has been identified as one of the specific causes of loss of extension. The incidence of cyclops syndrome is 2%-4% [17, 18], but there is still no understanding of its etiology. We speculate on the etiology and suggest some tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 21 publications
3
33
1
Order By: Relevance
“…One possible explanation may be that “harder” variants of lesions could represent a mechanical obstacle at the end of the knee extension, whereas “softer” variants, such as cyclopoid scars, do not affect the range of motion, as shown by Muellner et al [15]. However, other studies did not find any cartilage or bone tissue in cyclops lesions causing limited knee extension [10, 14]. Therefore, when evaluating a patient with clinical symptoms and decreased range of motion, the radiologist should be aware that the presence of a cyclops lesion could be both, a main finding or a finding without further clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…One possible explanation may be that “harder” variants of lesions could represent a mechanical obstacle at the end of the knee extension, whereas “softer” variants, such as cyclopoid scars, do not affect the range of motion, as shown by Muellner et al [15]. However, other studies did not find any cartilage or bone tissue in cyclops lesions causing limited knee extension [10, 14]. Therefore, when evaluating a patient with clinical symptoms and decreased range of motion, the radiologist should be aware that the presence of a cyclops lesion could be both, a main finding or a finding without further clinical relevance.…”
Section: Discussionmentioning
confidence: 99%
“…Although the origin of the fibrous tissue is uncertain, it has been suggested that the formation of the cyclops lesion is stimulated by debris from the drilling and preparation of the tibial tunnel [8, 11]. Even though this lesion was previously defined as localized arthrofibrosis [6, 12, 13], histologically the cyclops lesion is composed of disorganized fibrous connective tissue with a central region of granulation tissue and newly formed vessels [8, 10, 14, 15]. Repeated microtrauma may expose the graft collagen fibres, which can lead to productive inflammatory processes and to the formation of a cyclops nodule [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the tibial side, the ACL stump should be sufficiently removed to avoid development of a Cyclops lesion. 12,13,17,22 Residual ACL tissue removal may be expedited with the use of arthroscopic scissors, an osteotome, or arthroscopic electrocautery along with the shaver. The amount of bone that is removed from the notch is variable.…”
Section: Notch Preparationmentioning
confidence: 99%
“…Further study has indicated that the cause may be more multifactorial involving the location of the tibial tunnel, ACL stump remnants and potential microtrauma-induced neovascularization incurred during physical therapy. 6,7 Since that description, there have been few series describing this phenomenon. 7--11 Classically, cyclops syndrome occurs in the immediate postoperative course after ACL reconstruction.…”
Section: Introductionmentioning
confidence: 97%